Assessing the adoption of lopinavir/ritonavir oral pellets for HIV‐positive children in Zimbabwe. Issue 12 (13th December 2018) - Pasipanodya, Briony; Kuwengwa, Rudo; Prust, Margaret L; Stewart, Bethany; Chakanyuka, Christine; Murimwa, Tonderayi; Brophy, Jason; Salami, Olawale; Mushavi, Angela; Apollo, Tsitsi
Abstract: Introduction: Heat‐stable lopinavir/ritonavir (LPV/r) oral pellets were developed to overcome challenges with administration and storage experienced with previously available tablet and syrup forms of LPV/r prescribed to paediatric HIV patients. We report on the adoption of LPV/r pellets for infants living with HIV in the public sector antiretroviral therapy (ART) programme in Zimbabwe. Methods: Infants aged three months to three years who had been prescribed a LPV/r‐based regimen (including ART‐naïve patients) in fourteen facilities across the country were eligible to receive the pellets. Caregivers were counselled on the new formulation and provided with administration guides. A caregiver questionnaire was administered three to four months after the child initiated on pellets. Data were also extracted from patient ART records. Results and discussion: One hundred and fifty‐seven children were enrolled (median age: 21 months; interquartile range 11.8 to 29.4). Survey data from 74 caregivers were included for analysis. Eighty‐one per cent of the caregivers preferred pellets while 19% preferred the syrup formulation. Eighty‐nine per cent assessed their child's response to taking the pellets as good or very good. Overall, 46% did not report any challenges while 54% reported one or more challenges with using the pellets. Difficulties with administration included: poor taste (36%; 26 participants); swallowing pellets (16%; 12 participants); finishing the dose (14%; 10 participants); and opening the capsule (10%; seven participants). Caregivers who were not confident to instruct others on pellet administration were 5.64 (95% confidence interval 1.45 to 21.95, p = 0.013) times as likely to experience a challenge. Conclusions: A large proportion of caregivers preferred pellets to other formulations of LPV/r and reported a good response to pellets; however, they also reported challenges with administration. Counselling should focus on ensuring that caregivers can confidently administer pellets and are able to instruct others, to ensure high uptake and good adherence to treatment. LPV/r pellets may be an acceptable substitute for other available forms of LPV/r for eligible children under three years if they are currently on or in need of LPV/r‐containing regimens; however, challenges with administration still highlight the need for improved drug formulations for paediatric ART patients.